2015
DOI: 10.7860/jcdr/2015/14396.6803
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mobile Phone Dependence in Secondary School Adolescents

Abstract: Mobile Phone Dependence has been found to be an emerging public health problem. There is need to recognize and identify early the growing trends and negative consequences of inappropriate mobile phone use in young users so as to generate awareness, and plan educational and treatment interventions, if need be, so as to prevent a major public health concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
91
3
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 12 publications
10
91
3
6
Order By: Relevance
“…These results indicate high school students value the factors of "not being able to communicate" and "not being able to access information". The findings of this research are parallel with the findings of recent studies found in the literature, which report levels of nomophobia of between 35% and 73% on different levels of students around the world (Gezgin & Çakır, 2016;Nikhita, Jadhav, & Ajinkya, 2015;Sharma et al, 2015;Tavolacci et al, 2015;Yildirim et al, 2016). When the results of the study were analyzed in terms of gender, findings on nomophobia levels of high school students indicate that female students showed more nomophobic behaviors compared to male students.…”
Section: Conclusion and Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results indicate high school students value the factors of "not being able to communicate" and "not being able to access information". The findings of this research are parallel with the findings of recent studies found in the literature, which report levels of nomophobia of between 35% and 73% on different levels of students around the world (Gezgin & Çakır, 2016;Nikhita, Jadhav, & Ajinkya, 2015;Sharma et al, 2015;Tavolacci et al, 2015;Yildirim et al, 2016). When the results of the study were analyzed in terms of gender, findings on nomophobia levels of high school students indicate that female students showed more nomophobic behaviors compared to male students.…”
Section: Conclusion and Discussionsupporting
confidence: 81%
“…Another study conducted by Bivin et al (2013) with 547 students, the authors stated that a significant relationship was found between the style of smartphone use such as the duration of smartphone use, frequency of daily smartphone use, mobile Internet use on a smartphone, and the prevalence of nomophobia. Nikhita et al (2015) demonstrated that a significant relationship was found between dependence syndrome and the frequency and the duration of smartphone usage.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In the present study, it was found that the place where the adolescents used the Internet was associated with their self- there are concerns about their overuse (Vacaru, Shepherd, & Sheridan, 2014). Recently, the problematic use of mobile phones has attracted the attention of researchers and to some, is considered equivalent to drug addiction (Nikhita, Jadhav, & Ajinkya, 2015).…”
Section: Discussionmentioning
confidence: 59%
“…Along with the benefits of using mobile phones, there are concerns about their overuse (Vacaru, Shepherd, & Sheridan, ). Recently, the problematic use of mobile phones has attracted the attention of researchers and to some, is considered equivalent to drug addiction (Nikhita, Jadhav, & Ajinkya, ). Researchers have shown that the use of uncontrolled mobile phone is associated with loneliness (Tan, Pamuk, & Dönder, ), anxiety, depression (Tavakolizadeh et al, ), aggressive behaviors, insomnia, smoking, suicidality, and low self‐esteem (Yang, Yen, Ko, Cheng, & Yen, ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 2775 young adults from different parts of Europe, the highest numbers of nomophobia cases were found in northern (Finland and England) and southern Europe (Spain and Italy), although individually, the countries with higher values (greater than 30%) were Belgium, England, and France [30]. In India, a prevalence of 31.33% was found in a sample of 415 students, finding predictive factors such as sex, type of family, type of telephone used, average time of daily use, and total years of mobile phone use [31]. There is also high prevalence of nomophobia in special groups, such as medical oncologists [32], and university students during clases [33].…”
Section: Introductionmentioning
confidence: 99%